2022
DOI: 10.2147/ijgm.s350959
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic Analysis of Prognostic Value of Pyroptosis-Related Genes and Its Effect on Immune Cell Infiltration in Pancreatic Adenocarcinoma

Abstract: Purpose Pancreatic adenocarcinoma has a poor prognosis and chemotherapy has its limitation due to tumor heterogeneity. It is essential to find novel targets involving in tumorigenesis of pancreatic adenocarcinoma. Growing evidences indicated that pyroptosis is involved in tumorigenesis of many cancers, but the relationship between pyroptosis and pancreatic adenocarcinoma still remains to be elucidated. Our object is to explore whether pyroptosis-related different expression genes have association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Cao et al identified a series of long non-coding RNAs regulating the progression of pyroptosis and then established a pyroptosis-related lncRNA prognostic model for ovarian cancer (10). In addition, many reports confirmed that the pyroptosis level was significantly correlated to immunotherapy response in diverse types of human cancers such as glioma (11), pancreatic adenocarcinoma (12), and esophageal adenocarcinoma (13). These studies further determined the crucial value of pyroptosis in cancer, as well as the patient prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Cao et al identified a series of long non-coding RNAs regulating the progression of pyroptosis and then established a pyroptosis-related lncRNA prognostic model for ovarian cancer (10). In addition, many reports confirmed that the pyroptosis level was significantly correlated to immunotherapy response in diverse types of human cancers such as glioma (11), pancreatic adenocarcinoma (12), and esophageal adenocarcinoma (13). These studies further determined the crucial value of pyroptosis in cancer, as well as the patient prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that pyroptosis induced by caspase-1 can suppress the proliferation, migration, invasion, and cell spheroid formation of PC cells [ 26 ]. Some pyroptosis-related genes (PRGs) may be valuable research targets for PC, and their expression can be combined with specific immune characteristics to predict the survival benefit to patients [ 27 , 28 ]. However, researchers have speculated that pyroptosis can also play a dual role in the progression and therapeutic response of PC, but studies of pyroptosis in PC are scarce [ 29 ].…”
Section: Introductionmentioning
confidence: 99%